Recursos actuales y necesidades futuras: el caso de Santiaguito - del Castillo, Carlos (2007)
Santiaguito is a district in Peru’s northern Andes. In this paper we identify a number of opportunities to channel efforts towards its development. However, and as it is often the case, only the most explicit and obvious variables guide the development planning and management cycle. A non factual prospective analysis exercise allows to imagine a future situation that can be totally different from the originally proposed long-term vision. The available information is used with certain diagnosis and planning tools and then the outcome is compared with reality and hypothesis for the future.